The GluN2B-Glu413Gly NMDA receptor variant arising from a de novo GRIN2B mutation promotes ligand-unbinding and domain opening - Wells, Gordon (Proteins, 2018)
N-methyl-D-aspartate (NMDA) receptors are transmembrane glutamate-binding ion channels that mediate neurotransmission in mammals. NMDA receptor subunits are tetrameric complexes of GluN1 and GluN2A-D subunits, encoded by the GRIN gene family. Of these subunits, GluN2B is suggested to be required for normal development of the central nervous system. A mutation identified in a patient with developmental delay, E413G, resides in the GluN2B ligand-binding domain and substantially reduces glutamate potency by an unknown mechanism. GluN2B Gly413, though near the agonist, is not in van der Waals contact with glutamate. Visual analysis of the GluN2B structure with the E413G mutation modelled suggests that replacement of Glu with Gly at this position increases solvent access to the ligand-binding domain. This was confirmed by molecular modeling, which showed that the ligand is more mobile in GluN2B-E413G than WT GluN2B. Evaluation of agonist occupancy using random accelerated molecular dynamics (RAMD) simulations predicts that the glutamate exits the binding-site more rapidly for GluN2B-E413G than WT receptors. This analysis was extended to other binding-site mutations, which produced qualitative agreement between experimentally determined EC(50) values, deactivation time constants, and ligand motion within the binding-site. Furthermore, long sub-microsecond molecular dynamics simulations of the bi-lobed ligand-binding domain revealed that it adopted a cleft-open ligand-free state more often for GluN2B-E413G than wild-type GluN2B. This is consistent with the idea that L-glutamate binding is altered such that the ligand-binding domain occupies the open-cleft conformation associated with the closed channel.